Charter and Ordinances of the City of Syracuse 192 (1877) - (:unkn) unknown (My University, 1877)
Ch. 27, § 7: Any individual who shall carry about his or her person any dirk, bowie knife, sword or spear cane, pistol, revolver, slung-shot, jemme, brass knuckles, or other deadly or unlawful weapon, with the intent to do bodily harm to any other person or persons, shall be liable to a fine of not less than twenty-five dollars, and also to imprisonment not to exceed three months.
Keywords: CARRY - INTENT TO COMMIT CRIME